Talking about Hillsborough: 'Panic' as Discourse in Survivors' Accounts of the 1989 Football Stadium Disaster. (11th May 2013) - Cocking, Chris; Drury, John
ABSTRACT Popular representations of crowd behaviour in disasters are often characterised by irrationalist discourses, in particular 'mass panic' despite their rejection by current scientific research. This paper reports an analysis of four survivors' accounts of the 1989 Hillsborough disaster to investigate if and how they used the term 'panic'. Reference to 'panic' occurred frequently, but more detailed analysis found that their accounts did not match the classic criteria for 'mass panic' (e.g. uncontrolled emotion and selfish behaviour). Indeed, participants referred to 'orderly' behaviour, and cooperation, even when they said the threat of death was present. 'Panic' was therefore being used as a description of events that was not consistent. A discourse analysis of usage suggests that participants used 'panic' not only to convey feelings of fear and distress but also to apportion culpability towards the actions of the police who they considered responsible for the tragedy (as indeed recent independent research has confirmed). It is concluded that the term 'panic' is so deeply embedded in popular discourse that people may use it even when they have reason to reject its irrationalist implications. Alternative discourses that emphasise collective resilience in disasters are suggested. Copyright © 2013 John Wiley & Sons, Ltd.